A new mosaic der(18)t(1;18)(q32.1;q21.3) with developmental delay and facial dysmorphism - Young-Jin Choi; Eunsim Shin; Tae Sik Jo; Jin-Hwa Moon; Se-Min Lee; Joo-Hwa Kim; Jae-Won Oh; Chang-Ryul Kim; In Joon Seol (Korean Pediatric Society, 2016)
We report the case of a 22-month-old boy with a new mosaic partial unbalanced translocation of 1q and 18q. The patient was referred to our Pediatric Department for developmental delay. He showed mild facial dysmorphism, physical growth retardation, a hearing disability, and had a history of patent ductus arteriosus. White matter abnormality on brain magnetic resonance images was also noted. His initial routine chromosomal analysis revealed a normal 46,XY karyotype. In a microarray-based comparative genomic hybridization (aCGH) analysis, subtle copy number changes in 1q32.1-q44 (copy gain) and 18q21.33-18q23 (copy loss) suggested an unbalanced translocation of t(1;18). Repeated chromosomal analysis revealed a low-level mosaic translocation karyotype of 46,XY,der(18)t(1;18)(q32.1;q21.3)[12]/46,XY[152]. Because his parents had normal karyotypes, his translocation was considered to be de novo. The abnormalities observed in aCGH were confirmed by metaphase fluorescent in situ hybridization. We report this patient as a new karyotype presenting developmental delay, facial dysmorphism, cerebral dysmyelination, and other abnormalities.